Challenges Facing the Elderly in Accessing Health Services: A Case Study of Akheri Ward in Arumeru District, Arusha, Tanzania - Anande Kweka (Journal of Social and Community Development, 2025)
Globally, the ageing population is growing fast. Older adults face complex health needs and struggle to access appropriate care, especially in low- and middle-income countries. In Tanzania, rural elderly individuals face multiple barriers to healthcare. These include long distances to facilities, financial hardship, and a shortage of geriatric services. This study examined the challenges faced by elderly people in accessing healthcare in Akheri Ward, Arumeru District. The study employed a mixed-methods cross-sectional design involving 78 participants. The sample included elderly residents, community members, healthcare workers, and local leaders. Quantitative data came from structured questionnaires. Qualitative information was gathered through interviews, focus group discussions, and document reviews. Results showed that distance to facilities, poor transport options, and dependence on public health centers limited access. Socioeconomic barriers, including a lack of insurance, high medical costs, and low income, exacerbated the problem. Quality of care was mostly rated average. Long waits, limited explanations from providers, and a lack of geriatric specialists were common concerns. Ageism and weakening family support added further challenges. The study recommends decentralizing services, expanding mobile clinics, training more geriatric staff, improving financial protection, and reducing discrimination. These steps can help ensure that elderly people in rural Tanzania receive fair, respectful, and effective healthcare.